Human resources business process technical skill improvement - Aziza, Yumaika Nistia; Abdillah, Leon Andretti (Sinkron : jurnal dan penelitian teknik informatika, 2022)
One of the discussions in the field of information systems is business processes. Soft skill is something that is also very important in addition to academic knowledge. Soft skills are non-technical abilities such as being able to think critically and be able to manage time. In the world of work, companies are not only looking for prospective employees who only have good hard skills but also look at their soft skills. This is very important to be socialized and give knowledge to prospective students who will enter the world of work. One thing that can be done is training activities that can be followed by every student from various universities by participating in the Competent Indonesia National Movement (GNIK) program, this program specifically teaches soft skills and hard skills of human resources (HR) and human resource management (HRM). It consists of students from various islands in Indonesia. For the training, directions and provisions were given to carry out field practice using descriptive qualitative methods, namely observation, interviews, documentation, and final evaluation. This activity aims to provide understanding and mastery of soft skills to improve the quality of human resources. The results of this activity concluded that this activity was very helpful for participants in increasing their understanding and awareness in improving soft skills.